2022
DOI: 10.1073/pnas.2211861119
|View full text |Cite
|
Sign up to set email alerts
|

An insect-inspired asymmetric hinge in a double-layer membrane

Abstract: Insect wings are deformable airfoils, in which deformations are mostly achieved by complicated interactions between their structural components. Due to the complexity of the wing design and technical challenges associated with testing the delicate wings, we know little about the properties of their components and how they determine wing response to flight forces. Here, we report an unusual structure from the hind-wing membrane of the beetle Pachnoda marginata . The structure, a transver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…When we approach nature from an engineering perspective and focus on the mechanical design of natural systems, we uncover collective mechanical behaviours and emergent mechanical properties resulting from their specialized design. For example, observations of snake locomotion systems [9][10][11], fish body armours [12][13][14], gecko adhesive pads [15][16][17][18], insect flight systems [19][20][21][22][23][24], beetle fighting mechanisms [25,26] and many more indicate that natural mechanical systems consist of complicated material composition, nano-and micro-architecture and structural elements. This complicatedness can arise from two underlying design principles:…”
Section: Introductionmentioning
confidence: 99%
“…When we approach nature from an engineering perspective and focus on the mechanical design of natural systems, we uncover collective mechanical behaviours and emergent mechanical properties resulting from their specialized design. For example, observations of snake locomotion systems [9][10][11], fish body armours [12][13][14], gecko adhesive pads [15][16][17][18], insect flight systems [19][20][21][22][23][24], beetle fighting mechanisms [25,26] and many more indicate that natural mechanical systems consist of complicated material composition, nano-and micro-architecture and structural elements. This complicatedness can arise from two underlying design principles:…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Understanding the complex morphology of insect wings is not merely an academic pursuit in multiple scientific domains, such as biomechanics, animal behavior, physiology, and ecology, [ 2–7 ] but an inspiration for innovative technologies in the field of engineering. These include the development of robust load‐bearing structures, [ 8–10 ] bioinspired joints, [ 11–14 ] insect‐inspired hinges, [ 15 ] bioinspired wing, [ 16,17 ] insect‐inspired composites, [ 18,19 ] bioinspired attachment strategies, [ 20–22 ] and bioinspired grippers. [ 23 ]…”
Section: Introductionmentioning
confidence: 99%
“…[1] Understanding the complex morphology of insect wings is not merely an academic pursuit in multiple scientific domains, such as biomechanics, animal behavior, physiology, and ecology, [2][3][4][5][6][7] but an inspiration for innovative technologies in the field of engineering. These include the development of robust load-bearing structures, [8][9][10] bioinspired joints, [11][12][13][14] insect-inspired hinges, [15] bioinspired wing, [16,17] insectinspired composites, [18,19] bioinspired attachment strategies, [20][21][22] and bioinspired grippers. [23] As our understanding of the wing structures deepens, manual analysis methods face challenges in accurately capturing the complex geometric features to characterize wing morphology [24,25] comprehensively.…”
mentioning
confidence: 99%
“…[14][15][16][17][18] Understanding the scaling relationships between these parameters can provide insights into the mechanics of the wing and potentially inspire the development of bio-inspired materials and systems. [19][20][21][22][23] Previous studies have suggested that different Odonata species show different wing length allometries, meaning that the wing size changes at a different rate than the overall body size. [24][25][26] Other studies also suggest that the size of cells in the locust wing relates to the critical crack length, and the cellular structure of the insect wing is a crack resistance strategy to increase durability.…”
Section: Introductionmentioning
confidence: 99%